PERSEPSI MAHASISWA PROGRAM KAMPUS MENGAJAR TERHADAP MINAT MENJADI GURU PADA MAHASISWA STKIP AGAMA HINDU SINGARAJA, BALI - Kadek Heni Oktarina; Putu Desi Anggerina (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
ABSTRACT Kampus Mengajar is one of the programs of Merdeka Belajar Kampus Merdeka (MBKM), which is practiced by the Ministry of Education and Culture. The program provides a wide range of opportunities for students across Indonesia to contribute and influence the educational levels aimed at: primary schools, primary secondary schools, and high schools. The purpose of this article is to learn in detail about the students's perceptions of the Kampus Mengajar participants regarding their interest in becoming teachers after completing the program. This research uses a qualitative methodology. The data was obtained from observations, interviews, and documentation of six participants in the 5th and 6th of Kampus Mengajar who were students of the educational science study program. The focus of this research consists of five elements: motivation, unforgettable experiences, activity in the classroom, moral values, and impact. Based on the findings of observations and interviews, it was found that six participants had a similar desire to attend the Kampus Mengajar because they wanted to gain knowledge and experience as well as obtain cost-of-living assistance. They also carried out some of their activities, including literacy and numeration. This Kampus Mengajar also improves student skills, especially in social competence, management, empathy, problem-solving, and independence. After attending the Kampus Mengajar, students are more interested in being teachers. Keyword: Kampus Mengajar, Perception, Student’s Interest, Teacher